(3QSGdI aj GdOGA GdNajs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3bGd eMeO Hf RcQjG GdQGRj(B: (3jLH Ydi GdeJCNQjf aj GdReGf ceG bdfG aj UOQ hGMO ef cJHfG , Cf jJWdH eG CZadg GdChGFd hWhJg hCYeVJ GdcdGe ajg afPcQ eG GZadhG hfLeY eGaQbhG heG ffTQ eG CLedhG s
(3BNQgG (B:s
(3hejdg eY GddPI, agPG MUQ GdSHH GdaGYd dchf gPg GdYdI , hbO ENJUQfGg bOQ LgOfG s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B105 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGj (B(4679) s
Keywords: (3GdWHs